Improvement of the female mouse computational model developed at CDTN - Rodrigues Joana D’Arc Souza; Mendes Bruno Melo; Leite Christiane Silva; Bispo Ana Carolina de Araujo; Ferreira Andrea Vidal; Silva Juliana Batista; Roivainen Anne; Teuho Jarmo (Brazilian Journal of Development, 2025)
Small animals, such as mice, have been used in experiments involving ionizing radiation. New preclinical experimental methods often include extensive imaging (MicroCT and/or PET/SPECT) that can result in absorbed dose values considerably high. In addition, assays with theranosticsradiopharmaceuticals administered in small animals have been used to determine the main potential adverse effects and the therapeutic efficacy. For all these mentioned cases, the precise quantification of absorbed doses and the determination of energy deposition patterns are of fundamental importance to qualify or exclude potential radiobiological effects that may interfere with in vivo experiment results. Thus, the development and improvement of mouse phantoms is essential for good small animal dosimetry. In 2021, our group segmented and implemented a female C57BL mouse phantom, called FM_BRA, in the MCNP. The objective of this work was to review the segmentation of the FM_BRA computational model and to identify and segment new organs for an improved version of this phantom. Three different researchers segmented different organs of the model. The masses of the segmented organs were compared with those of the first version. Information on mass or volume of organs from different mouse strains, and more specifically from the C57BL strain, was also obtained from the literature for comparison and to aid in segmentation. The mice image representing a female mouse of the C57BL strain weighing 26 g were kindly provided by the Turku Center for Disease and were manually segmented. The software GIMP® 2.10 was used to select and segment each organ/tissue. The IMAIOS-VET Anatomy website was used as an anatomical basis for the identification of organs/tissues. The IMAGEJ® software was applied to assemble the segmented images into a 3D stack and to convert the segmented images into binary files. The volumes of the segmented organs were measured with a C++ in house program. Corresponding human tissue densities provided in ICRP 110 were used to calculate organ mass from the calculated volumes. Data were compared with literature reports. The number of segmented organs increased from 20 in the old model to 33 in the new models. The masses of the organs segmented in this work, by the different researchers, showed agreement in most cases. However, organs such as the small intestines, bones and trachea still deserve a new round of reviewing.